2010
DOI: 10.1007/s12011-010-8684-3
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Nutrient Medium for In Vitro Somatic Embryo Induction in Plantago ovata Forsk

Abstract: A nutrient medium has been formulated by altering the macro- and micro-elemental concentration in the culture medium for in vitro somatic embryo induction of economically important medicinal plant Plantago ovata Forsk .A comparison was made between induced embryos with normal embryos (produced in Murashige and Skoog (MS) medium) to observe frequency of embryo induction and also to determine regeneration efficiency. In the present investigation, three different media have been formulated. Among them, FM3 (formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
(77 reference statements)
1
0
0
Order By: Relevance
“…2,4-D in combination with KIN has earlier been reported to induce callus formation in P. ovata and related species [10,12,13]. Our findings related to the nature of callus were confirmed with the reports of Saha et al [14] wherein they have reported that 2,4-D and KIN were more effective for callus induction and proliferation from leaf explants of P. ovata. In a recent study on in vitro culturing and callogenesis of Solanum tuberosum, it was illustrated that variations in hormonal concentrations affect callus development and micropropagation [15].…”
supporting
confidence: 91%
“…2,4-D in combination with KIN has earlier been reported to induce callus formation in P. ovata and related species [10,12,13]. Our findings related to the nature of callus were confirmed with the reports of Saha et al [14] wherein they have reported that 2,4-D and KIN were more effective for callus induction and proliferation from leaf explants of P. ovata. In a recent study on in vitro culturing and callogenesis of Solanum tuberosum, it was illustrated that variations in hormonal concentrations affect callus development and micropropagation [15].…”
supporting
confidence: 91%